2013
DOI: 10.1371/annotation/b9f7e31f-460e-4fef-bfdf-038fadbf4c1b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: 3-D Visualization and Quantitation of Microvessels in Transparent Human Colorectal Carcinoma

Abstract: Microscopic analysis of tumor vasculature plays an important role in understanding the progression and malignancy of colorectal carcinoma. However, due to the geometry of blood vessels and their connections, standard microtomebased histology is limited in providing the spatial information of the vascular network with a 3-dimensional (3-D) continuum. To facilitate 3-D tissue analysis, we prepared transparent human colorectal biopsies by optical clearing for in-depth confocal microscopy with CD34 immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Starting from 2009, the group led by Tang has performed copacetic series of studies appraising versatility of FocusClear (RI = 1.45–1.46) for both basic and clinical research on intestines. In a sequence of studies this group convincingly demonstrated that FocusClear could be effectively applied to image every tissue type of murine and human intestines, with a cellular resolution in 3D fashion, allowing discrimination of epithelium, blood vessels, and nervous tissue, under both normal and pathological conditions ( Figure ) . This imaging has eventually led to, for example, identification of a new, perivascular type of interstitial cells of Cajal in human colon (Figure a) and enabled visualization of the enteric glia…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 98%
See 1 more Smart Citation
“…Starting from 2009, the group led by Tang has performed copacetic series of studies appraising versatility of FocusClear (RI = 1.45–1.46) for both basic and clinical research on intestines. In a sequence of studies this group convincingly demonstrated that FocusClear could be effectively applied to image every tissue type of murine and human intestines, with a cellular resolution in 3D fashion, allowing discrimination of epithelium, blood vessels, and nervous tissue, under both normal and pathological conditions ( Figure ) . This imaging has eventually led to, for example, identification of a new, perivascular type of interstitial cells of Cajal in human colon (Figure a) and enabled visualization of the enteric glia…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 98%
“…Copyright 2014, Elsevier. b,c) Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International License ( http://creativecommons.org/licenses/by/4.0/) . Copyright 2013, The Authors.…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 99%